The emotional impact of tennis on young players and their parents – a feelings-based approach - Piquer-Piquer, Ana (2025)
Emotions and feelings are present in all areas of human life—not least in sports and physical activity. Tennis, mainly due to the fact that it is an individual sport and to the characteristics of the game, lends itself to a great variety of emotions. Young or school-age players, in addition, are heavily influenced by their parents in terms of their emotions. In order to carry out an analysis of the feelings and emotions related to playing tennis that is more reliable and objective than those carried out up to now, the methodology of feelings analysis combined with a qualitative analysis was applied, in order to increase the quality of the results obtained. For this purpose, personal interviews of 9 tennis players and 8 parents were conducted, which were transcribed and analyzed with the Syuzhet package in the R programming language. The results showed that the emotions most frequently reported by players and their parents were positive (in this case, confidence and anticipation). These emotions were linked to the social relationships experienced in tennis, as well as to the practice of the sport and values it conveys. On the other hand, negative emotions such as sadness and fear were reported, related to the contexts of competition, disappointment with performance and the parents’ empathy towards their children’s nervousness. Generally speaking, the practice of tennis brings with it many emotional benefits, although it can involve certain risks at an early age when it is carried to an extreme.